Rice Field Fishery Database, 2012-2015 - Sean, Vichet; Kim, Miratori; Brooks, Alan; Try, Vanvuth; MacDonell, Hillary (2024)
The current database is the result of the merging of three major databases containing Rice Field Fishery Enhancement Project data collected by WorldFish from November 2012 to January 2016. The project had the goal to increase the productivity and the sustainability of the rice field fishery system. Interventions and public awareness took place in forty community fish refuges (CFR) around the Tonle Sap Lake and among the communities living nearby those CFR. To evaluate the impact of the actions undertaken, biological surveys were conducted and households living nearby were interviewed on a regularly base about their livelihood.